Effect of exercise-based cancer rehabilitation via telehealth: a systematic review and meta-analysis - Batalik, Ladislav; Chamradova, Katerina; Winnige, Petr; Dosbaba, Filip; Batalikova, Katerina; Vlazna, Daniela; Janikova, Andrea; Pepera, Garyfallia; Abu-Odah, Hammoda; Su, Jing Jing (BMC cancer, 2024)
PURPOSE: Exercise-based cancer rehabilitation via digital technologies can provide a promising alternative to centre-based exercise training, but data for cancer patients and survivors are limited. We conducted a meta-analysis examining the effect of telehealth exercise-based cancer rehabilitation in cancer survivors on cardiorespiratory fitness, physical activity, muscle strength, health-related quality of life, and self-reported symptoms. METHODS: PubMed, Web of Science, and reference lists of articles related to the aim were searched up to March 2023. Randomized controlled clinical trials were included comparing the effect of telehealth exercise-based cancer rehabilitation with guideline-based usual care in adult cancer survivors. The primary result was cardiorespiratory fitness expressed by peak oxygen consumption. RESULTS: A total of 1510 participants were identified, and ten randomized controlled trials (n = 855) were included in the meta-analysis. The study sample was 85% female, and the mean age was 52.7 years. Meta-analysis indicated that telehealth exercise-based cancer rehabilitation significantly improved cardiorespiratory fitness (SMD = 0.34, 95% CI 0.20, 0.49, I2 = 42%, p < 0.001) and physical activity (SMD = 0.34, 95% CI, 0.17, 0.51, I2 = 71%, p < 0.001). It was uncertain whether telehealth exercise-based cancer rehabilitation, compared with guideline-based usual care, improved the quality of life (SMD = 0.23, 95%CI, -0.07, 0.52, I2 = 67%, p = 0.14) body mass index (MD = 0.46, 95% CI, -1.19, 2.12, I2 = 60%, p = 0.58) and muscle strength (SMD = 0.07, 95% CI, -0.14, 0.28, I2 = 37%, p = 0.51). CONCLUSION: This meta-analysis showed that telehealth exercise cancer rehabilitation could significantly increase cardiorespiratory fitness and physical activity levels and decrease fatigue. It is uncertain whether these interventions improve quality of life and muscle strength. High-quality and robust studies are needed to investigate specific home-based exercise regimens in different cancer subgroups to increase the certainty of the evidence.
Keywords: svalová síla; Telemedicine; Humans; Cancer rehabilitation; lidé středního věku; Cancer Survivors; Quality of Life; Cardiorespiratory Fitness; Female; Exercise Therapy; Home-based exercise; lidé; přežívající onkologičtí pacienti; Exercise-based rehabilitation; Telerehabilitation; randomizované kontrolované studie jako téma; kvalita života; Muscle Strength; telemedicína; ženské pohlaví; Telehealth; Male; Randomized Controlled Trials as Topic; Middle Aged; Neoplasms; nádory; Exercise; mužské pohlaví; terapie cvičením; kardiorespirační zdatnost; cvičení; telerehabilitace